The role of sediments as a source of metals in river catchments. - Chon,HS; Ohandja,D-G; Voulvoulis,N (Chemosphere, 2012)
Aquatic sediments are a known source of pollutants, but their impact on the quality of overlying waters is not easily quantified. Sediments are generally considered to behave as a sink for pollutants such as heavy metals in the aquatic environment, frequently acting as a source for their presence in waters, with implications for catchment management. This study aimed to calculate the contribution of sediments to metal levels in overlying waters, helping understand their role as a source of metals in river catchments. An aquivalence mass balance approach was modified to take into account both natural and anthropogenic influences and applied to assess sediment contribution in a reach of the River Yare in the UK. The rates of total metal transport from sediments to overlying waters were estimated to be 29.89gd(-1) for cadmium (Cd), 1633.39gd(-1) for lead (Pb), 8.29gd(-1) for mercury (Hg) and 357.56gd(-1) for nickel (Ni). The results from the case study demonstrated that sediments could be a significant source of metal emissions in river catchments. The calculations proposed in the paper could be useful in developing strategies for sediment management, not only to improve and/or maintain quality of sediments but also to inform the selection of measures of pollution control for the catchment.